EFL Teachers’ Voices on the Implementation of Differentiated Instruction in the Indonesian Educational Context - Andi Taperiani; Baso Jabu; Andi Muliyati (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
Indonesia's evolving education system, marked by curriculum reforms like the Merdeka Curriculum, aims to foster student potential by embracing flexibility and diversity. Aligned with national education goals and pedagogical theories, differentiated instruction plays a crucial role in addressing students' unique needs, ensuring a more inclusive and effective learning experience. This study examines (1) the strategies used by an English teacher in implementing differentiated instruction as well as (2) students' perceptions toward the implementation of differentiated instruction at SMAN 1 Balaesang in Donggala regency. Employing a mixed-method research design, the researcher used purposive sampling to select a tenth-grade English teacher and 31 students taught by this teacher as participants. Data were collected through observations, interviews, and questionnaires, then analyzed both qualitatively and quantitatively using a descriptive approach. The findings revealed that the teachers’ strategies focused on three key stages: planning, implementation, and evaluation. In the planning stage, diagnostic tests and curriculum analysis were conducted to tailor instruction. During implementation, differentiation was applied to content, process, and product to meet students' diverse needs. Lastly, evaluation involved observations and assessments to monitor student progress and effectiveness of instruction. Additionally, the study found that 77.42% of students had a positive perception of differentiated instruction in learning English. A variety of teaching approaches, student choice, and adaptive strategies contributed to increased engagement. To effectively meet students’ needs, teachers continuously refine differentiated instruction by integrating diverse activities, utilizing technology, and personalizing assessments.